2017
DOI: 10.4014/jmb.1608.08032
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation, Purification, and Characterization of Five Active Diketopiperazine Derivatives from Endophytic Streptomyces SUK 25 with Antimicrobial and Cytotoxic Activities

Abstract: In our search for new sources of bioactive secondary metabolites from sp., the ethyl acetate extracts from endophytic SUK 25 afforded five active diketopiperazine (DKP) compounds. The aim of this study was to characterize the bioactive compounds isolated from endophytic SUK 25 and evaluate their bioactivity against multiple drug resistance (MDR) bacteria such as and spp., and their cytotoxic activities against the human hepatoma (HepaRG) cell line. The production of secondary metabolites by this strain was opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 0 publications
3
24
0
1
Order By: Relevance
“…In line with several previous studies, these groups of chemicals were also reported in the bacterial fermentation broth or extracts derived from Actinomycetes and Streptomyces sp. For instance, dimethyltrisulfide ( 1 ) (Groenhagen, Maczka, Dickschat, & Schulz, ), trimethylpyrazine ( 2 ) (Citron, Barra, Wink, & Dickschat, ), 2‐acetylpyrrole ( 3 ) (Morgenstern, Paetz, Behrend, & Spiteller, ), pyrazine,2,5‐dimethyl‐3‐(3‐methylbutyl) ( 4 ) (Citron et al, ), phenol,2,4‐bis(1,1‐dimethylethyl)‐ ( 8 ) (Kumar, Duraipandiyan, & Ignacimuthu, ), benzoic acid,4‐ethoxy‐,ethyl ester ( 9 ) (Sharma, Goel, Dureja, & Uniyal, ), (3R,8aS)‐3‐methyl‐1,2,3,4,6,7,8,8a‐octahydropyrrolo[1,2a]pyrazine‐1,4‐dione ( 13 ) (Tan et al, ), pyrrolo[1,2a]pyrazine‐1,4‐dione, hexahydro ( 14 ) (Ser, Palanisamy, et al, ), 1,4‐diaza‐2,5‐dioxo‐3‐isobutyl bicyclo[4.3.0]nonane ( 15 ) (Ser, Ab Mutalib, et al, ), 9H‐Pyrido[3,4‐b]indole ( 16 ) (Tan, Ser, et al, ), 2,5‐piperazinedione, 3‐(1‐methylethyl)‐6‐(phenylmethyl)‐ ( 17 ) (Alshaibani et al, ), 3‐benzyl‐1,4‐diaza‐2,5‐dioxobicyclo[4.3.0]nonane ( 18 ) (Jog, Pandya, Nareshkumar, & Rajkumar, ; Sharma, Kalita, & Thakur, ) and phenol,2,2′‐methylenebis[6‐(1,1‐dimethylethyl)‐4‐methyl‐ ( 19 ) (Tan, Ser, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with several previous studies, these groups of chemicals were also reported in the bacterial fermentation broth or extracts derived from Actinomycetes and Streptomyces sp. For instance, dimethyltrisulfide ( 1 ) (Groenhagen, Maczka, Dickschat, & Schulz, ), trimethylpyrazine ( 2 ) (Citron, Barra, Wink, & Dickschat, ), 2‐acetylpyrrole ( 3 ) (Morgenstern, Paetz, Behrend, & Spiteller, ), pyrazine,2,5‐dimethyl‐3‐(3‐methylbutyl) ( 4 ) (Citron et al, ), phenol,2,4‐bis(1,1‐dimethylethyl)‐ ( 8 ) (Kumar, Duraipandiyan, & Ignacimuthu, ), benzoic acid,4‐ethoxy‐,ethyl ester ( 9 ) (Sharma, Goel, Dureja, & Uniyal, ), (3R,8aS)‐3‐methyl‐1,2,3,4,6,7,8,8a‐octahydropyrrolo[1,2a]pyrazine‐1,4‐dione ( 13 ) (Tan et al, ), pyrrolo[1,2a]pyrazine‐1,4‐dione, hexahydro ( 14 ) (Ser, Palanisamy, et al, ), 1,4‐diaza‐2,5‐dioxo‐3‐isobutyl bicyclo[4.3.0]nonane ( 15 ) (Ser, Ab Mutalib, et al, ), 9H‐Pyrido[3,4‐b]indole ( 16 ) (Tan, Ser, et al, ), 2,5‐piperazinedione, 3‐(1‐methylethyl)‐6‐(phenylmethyl)‐ ( 17 ) (Alshaibani et al, ), 3‐benzyl‐1,4‐diaza‐2,5‐dioxobicyclo[4.3.0]nonane ( 18 ) (Jog, Pandya, Nareshkumar, & Rajkumar, ; Sharma, Kalita, & Thakur, ) and phenol,2,2′‐methylenebis[6‐(1,1‐dimethylethyl)‐4‐methyl‐ ( 19 ) (Tan, Ser, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Liquid and gas chromatography are irreplaceable instruments for the separation of highly complex bacterial crude extracts [ 261 , 262 , 263 ]. Another evolving analytical separation technique that has already proven its impact in phytochemistry is supercritical fluid chromatography (SFC) [ 264 ].…”
Section: Metabolomics For the Discovery Of New Antibiotics Producementioning
confidence: 99%
“…Based on ethnobotanical information, C. fruticosa is used as a hemostatic and also used to treat diarrhea, sore throat, neck pain, toothache, laryngitis, and mammary gland infections (Fouedjou et al 2014;Fouedjou et al 2016). Plants used in traditional medicine around the world are studied for their ability as host for endophytic fungi that have antimicrobial potential, and recent developments reported that endophytic fungi are a potential reservoir of bioactive compounds useful for medicinal exploitation (Alshaibani et al 2017;Liang et al 2012;Chi et al 2019).…”
Section: Introductionmentioning
confidence: 99%